Metastasis to the rectum: A systematic review of the literature. Issue 4 (April 2022) - Janjic, Olivier; Labgaa, Ismail; Hübner, Martin; Demartines, Nicolas; Joliat, Gaëtan-Romain
Abstract: Background: Metastatic spread to the rectum is a rare finding, and management of rectal metastases (RM) is not standardized. The aim of the present study was to review the evidence on diagnosis, management and outcomes of RM. Methods: A computerized literature search through MEDLINE/PubMed, Embase and the Cochrane databases was performed, applying a combination of terms related to RM. Articles and abstracts were screened and final selection was done after cross-referencing and by use of predefined eligibility criteria. Results: Final analysis was based on 99 publications totaling 162 patients with RM from 16 different primary tumors. Most common origins of RM were breast (42 patients), stomach (38 patients), and prostate (16 patients). RM occurred metachronously in the majority of patients (77%). The main treatment was surgical resection (n = 32), followed by chemotherapy (n = 16). Median overall survival for breast RM, stomach RM, and prostate RM were 24 months (95% CI 9-39 months), 7 months (95% CI 0-14 months), and 24 months (95% CI 7-41 months), respectively. Conclusion: RM is a rare and highly heterogeneous condition. Surgical treatment appears to be a valuable treatment option in selected patients, while overall prognosis depends mainly on the primary tumor.